2001
DOI: 10.1182/blood.v98.6.1727
|View full text |Cite
|
Sign up to set email alerts
|

Catheter-related deep venous thrombosis in children with hemophilia

Abstract: Central venous catheters (CVCs) are a common adjunct to hemophilia therapy, but the risk of CVC-related deep venous thrombosis (DVT) in hemophiliacs is not well defined. In a previous study, 13 patients with CVCs had no radiographic evidence of DVT. However, recent abstracts and case studies demonstrate that DVT does occur. Therefore, this study sought to determine the frequency of DVT in children with hemophilia and long-term CVCs and to correlate venographic findings with clinical features. All hemophilia pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
141
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(150 citation statements)
references
References 19 publications
8
141
0
1
Order By: Relevance
“…In one other patient thrombophilia screening awaits parental consent. Similar to patient number 2 in Journeycake et al, 1 the heterozygous factor V 20210GϾA mutation was present in 2 of our 7 patients. Additionally, 4 patients were treated with factor (F) VIII/vWF concentrates, and 1 child each received purified FVIII, recombinant VIIa, purified FVIII, and recombinant FVIII, respectively.…”
supporting
confidence: 88%
See 2 more Smart Citations
“…In one other patient thrombophilia screening awaits parental consent. Similar to patient number 2 in Journeycake et al, 1 the heterozygous factor V 20210GϾA mutation was present in 2 of our 7 patients. Additionally, 4 patients were treated with factor (F) VIII/vWF concentrates, and 1 child each received purified FVIII, recombinant VIIa, purified FVIII, and recombinant FVIII, respectively.…”
supporting
confidence: 88%
“…Although bleeding symptoms correlate with the levels of the remaining factor activity, it is reported that some hemophilic subjects with factor VIII levels below 1% do not all bleed with the same severity, and in rare cases of severe HA, thrombotic episodes have also been reported in childhood. [1][2][3][4][5][6][7][8] Since the reported symptomatic vascular accidents in hemophiliacs are, in the majority of cases, related to central venous lines (CVLs), we have read with interest the paper by Journeycake et al 1 Their data demonstrated that hemophiliacs with tunneled subclavian CVLs in place for more than 48 months had abnormal venograms. 1 In addition, 5 of 15 hemophiliacs (33.3%) had symptomatic deep venous thrombosis (DVT) related to the CVLs; 3 further patients (20%) with signs of DVT on contrast venography had no clinical problems.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…8,11,12 The need for frequent dosing, especially in pediatric patients, presents challenges in terms of repeated venous access that may necessitate the placement of indwelling catheters that is associated with frequent complications such as thromboses and infections. 13,14 Furthermore, frequent dosing interrupts daily activities and therefore, lack of compliance with a frequent injection regimen is one of the most commonly cited reasons for failure of prophylaxis. 15 Similar to patients with mild or moderate hemophilia B, patients with severe hemophilia B would also benefit from a single effective dose, instead of multiple doses, when they experience breakthrough bleeding episodes during prophylaxis.…”
Section: Introductionmentioning
confidence: 99%
“…23 The majority of CVC-VTE are sub-clinical and not accompanied by a swollen, painful, or erythematous extremity. [24][25][26] In a prospective, multicenter cohort study of children with acute lymphoblastic leukemia (ALL), 29 of 85 (34%) developed CVC-VTE within the first month after CVC placement, but only 1 of these 29 patients had clinical symptoms. No patient tested positive for the factor V Leiden or prothrombin gene mutation.…”
Section: Catheter-related Thrombosismentioning
confidence: 99%